Analisis Regresi Pada Tren Perubahan Garis Pantai di Pantai Krui dari Digitasi Citra Landsat - Satriyo Panalaran; Trika Agnestasia Br Tarigan; Hendra Achiari (Journal of Science and Applicative Technology, 2019)
Krui is a capital of Pesisir Barat Regency of Lampung Province which has important values on residential areas, business centers, government centers, and tourism destination. Kruis coast is adjacent to the Indian Ocean, which has the high wave characteristic cause the dynamic coastal process similarly to other sandy beaches on the west coast of Sumatera Island. The coastal process can be shown in the form of either coastline accretion due to sedimentation or shoreline reduction caused by the phenomenon of erosion and abrasion. The coastal process can be observed as a natural process to achieve an equilibrium of sediment transport along the coast. Also, Shoreline change is influenced by the height waves and the direction of incoming waves towards onshore depending on the season. The aims of this study is to get an overview of the shoreline changes that occur on the Krui Coast. Then it can be predicted the position of the coastline in the future. The regression model was chosen to estimate the position of shoreline in the future by utilizing a set of time-series data that refers to shoreline change within certain periods. Digitized Landsat-7 ETM+ satellite imagery is conducted in order to obtain shoreline position data in every year determinate as historical data. Based on this study, the rate of shoreline change in Krui Coast is within range of 0,12 meters/year to 41,35 meters/year, where is the shoreline change tends to increase. Keywords: Digitization, Landsat, Shoreline, Regression